The endocrine heart: from the bench to the bedside and back to the bench - de Bold, Adolfo J. (2005)
Two polypeptide hormones are produced, stored and secreted in a regulated manner by cardiac muscle cells (cardiocytes) of the atria of the heart of mammals. These are atrial natriuretic factor (ANF)1-3 and brain natriuretic peptide (BNP).4 They form part of a family of hormones referred to as natriuretic peptides (NP). A third member: CNP, is not natriuretic and is not produced by cardiocytes. Both ANF and BNP are co-stored in atrial cardiocytes in storage granules referred to as specific atrial granules. Some confusion has recently developed in the clinical literature as to the precise cell type where this secretory function resides, as well as to the peptide storage form and the location of the secretory function, which, of late, is often quoted as being the atria for ANF and the ventricular muscle for BNP. By Northern blot analysis, immunocytochemistry, in situ hybridization, radioimmunoassay and oligonucleotide array, ANF and BNP are far more abundant in the atria than the ventricles. In fact, the level of expression of NP in the normal ventricles is negligible compared to that of the atria.